Characterization of culturable airborne bacteria and antibiotic susceptibility profiles of indoor and immediate-outdoor environments of a research institute in Ghana [version 2; peer review: 2 approved] - Isawumi Abiola; Adiza Abass; Samuel Duodu; Lydia Mosi (AAS Open Research, 2018)
Background: The study was conducted to determine the bacterial composition and antibiotic susceptibility profiles of a research institute at the University of Ghana where workers and students spend about 70-85% of their lives in indoor and immediate-outdoor environments. This is imperative as one-third of the recognized infectious diseases are transmitted through airborne-route. Furthermore, the increasing rate of bacterial antimicrobial resistance associated with such environments poses serious public health challenges. Methods: A total of 42 airborne samples were collected from eight major sites at the Department of Biochemistry, Cell and Molecular Biology (BCMB), using passive bacterial sampling techniques. Standard phenotypic microbiological procedures were used to characterize the isolates. Antibiotic susceptibility profiles were determined using standard disk diffusion method and guidelines of Clinical and Laboratory Standards Institute (CLSI). Results: Four groups of bacterial isolates were identified from the total samples collected with Gram positive bacilli as the most common. All the isolates showed resistance to beta lactam and sulfonamide classes of antibiotics with full resistance (100%) to ampicillin and penicillin. In total, seven different anti-biotypes were observed with the highest susceptibility displayed towards tetracycline and gentamycin. Significantly, the various air sampling sites of the institute indicated the presence of bacteria with the majority showing multiple antibiotics resistance. Conclusions: Although the recovery of bacteria from supposed sterile environments calls for attention, the observed low contamination rate as compared to the WHO standard suggests a minimum risk of exposure of students and workers to airborne microbial contamination.